Iron-facilitated dynamic active-site generation on spinel CoAl₂O₄ with self-termination of surface reconstruction for water oxidation - Wu, Tianze (2021)
The development of efficient and low-cost electrocatalysts for the oxygen evolution reaction (OER) is critical for improving the efficiency of water electrolysis. Here, we report a strategy using Fe substitution to enable the inactive spinel CoAl2O4 to become highly active and superior to the benchmark IrO2. The Fe substitution is revealed to facilitate surface reconstruction into active Co oxyhydroxides under OER conditions. It also activates deprotonation on the reconstructed oxyhydroxide to induce negatively charged oxygen as an active site, thus significantly enhancing the OER activity of CoAl2O4. Furthermore, it promotes the pre-oxidation of Co and introduces great structural flexibility due to the uplift of the oxygen 2p levels. This results in the accumulation of surface oxygen vacancies along with lattice oxygen oxidation that terminates as Al3+ leaches, preventing further reconstruction. We showcase a promising way to achieve tunable electrochemical reconstruction by optimizing the electronic structure for low-cost and robust spinel oxide OER catalysts.